EFL Students’ Perceptions on the Use of TikTok Videos in Increasing Speaking Skills - Farhan Aulady; Silih Warni (Institut Agama Islam Negeri Palopo, 2024)
The research delves into a comprehensive exploration of students' perceptions concerning the efficacy of TikTok as a tool for improving their oral communication skills. Employing a rigorous quantitative methodology, the researcher meticulously selects three cohorts of tenth-grade students to serve as the study's sample population. The data collection process entails the systematic application of a Likert scale. Subsequently, the amassed data undergoes a meticulous analysis, conducted through sophisticated tabulation procedures within the Microsoft Excel platform. The results of this analysis yield compelling insights, revealing a substantive and statistically significant positive association between the utilization of TikTok and the enhancement of students' oral communication proficiencies. Moreover, the results shed light on an interesting aspect of students' views on TikTok; a significant number of people exhibit a highly optimistic perspective. Many students express enthusiasm for incorporating TikTok into their English language learning journey. This insight emphasizes how TikTok can create an interactive and captivating learning atmosphere, boosting the development of crucial speaking skills among school students.